Om te preek oor die opstanding van Christus: eksegetiese en homiletiese riglyne vir die prediking van 1 Korintiërs 15:1-11 - Tolmie, DF (Nederduitse Gereformeerde Teologiese Tydskrif, 2003)
After a brief look at the situating within which 1 Corinthians was written, important exegetical issues in 1 Corinthians 15:1-11 are discussed. This is followed by a discussion of the resurrection of Christ from three perspectives: the Jewish background of the notion, its place within Paul’s theology, and the way in which it is handled in Historical Jesus research. Finally, some homiletical guidelines (both textual and contextual) are provided.